Громадська активність населення міст та роль в ній екологічної інформації - Самойленко, Наталія Миколаївна; Рассоха, Олексій Миколайович; Аверченко, Валентина Іллівна; Мамедова, Ольга Олегівна (НТУ "ХПІ", 2015)
Розглянуто питання участі громадськості у вирішенні екологічних проблем міста. На основі результатів анкетування визначений рівень поінформованості населення про екологічний стан міста та готовності представників громадськості до ініціативної участі у його покращанні. Охарактеризовані напрямки активізації поширення екологічної інформації серед містян як основи для формування їх екологічної поведінки і громадської активності. Відмічена необхідність посилення комунікаційного процесу між громадськими радами і населенням.

The current trend of growth of urbanized areas and the deteriorating environmental situation in their is shows. The problems of community participation in making decisions on environmental concerns of the city are considered. Based on the results of questionnaire the level of public awareness about the ecological state of the city is defined, as well as preparedness of initiative citizens in improving it. Insufficient dissemination of ecological information among towns people was observed. This fact is an obstacle for the formation of environmental awareness of inhabitants of the city, as well as in the implementation of practical activities to protect the environment in their place of residence. In order to increase their awareness, joint work is needed for all participants of information process in society: authorities of environmental management, enterprises, public service organizations and others. Revitalization of the work of community councils operating in Ukraine with state authorities is appropriate. This will expand the functions of the citizens in finding solutions for ecologically important social tasks. Thus, it is necessary to increase the level of dissemination of information about the activities of such councils in the population, as well as significantly improve the communications between them.
Public activity of the population of cites and the role of environmental information therein
Keywords: стан екологічний; урбанізація; анкетування; urbanized territories; ecological condition; questionnaire; ecological informing; community council